Numerical calculation of the thermal-hydraulic characteristics in a once-through steam generator based on a coupled boundary. (5th February 2019) - Shi, Jianxin; Yang, Longbin; Sun, Baozhi; Li, Yanjun; Yu, Xiang; Zhang, Peng
Highlights: Flow and heat transfer equations of tube, primary and secondary sides are developed. Application range of the model is extended to actual coupled heat transfer cases. Axial wall temperatures under coupled boundary and constant heat flux are compared. Key thermal-hydraulic parameters under actual coupled boundary are obtained. Abstract: The operational processes of the primary side, secondary side, and heat transfer tubes of a once-through steam generator were numerically modeled through conservation equations for the flow and heat transfer processes, where the dryout criterion was modified to extend the application range of the model to accurately portray coupled heat transfer conditions. The results show that the proposed model and coupled method was used to accurately calculate the actual operation. The secondary wall temperature gradient at dryout position, based on a coupled boundary, is approximately several tens of degrees Kelvin per meter (K/m), while the value using a constant heat flux method reaches several hundreds of degrees Kelvin per meter (K/m). The primary and secondary pressures decrease approximately linearly and non-linearly along their own flow directions, respectively. The occurrence of dryout leads to a deviation from thermodynamic equilibrium in the post-dryout region, where the actual steam quality rises slowly with a smaller gradient compared to that in the pre-dryout region. Therefore, the acceleration of steam-liquid has less effect on total pressure drop and on the decrease in secondary pressure gradient.